2022
DOI: 10.1103/physrevlett.128.217203
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive beyond Room-Temperature Ferromagnetism in a Doped van der Waals Magnet

Abstract: Two-dimensional (2D) magnetic van der Waals materials provide a powerful platform for studying fundamental physics of low-dimensional magnetism, engineering novel magnetic phases, and enabling ultrathin and highly tunable spintronic devices. To realize high quality and practical devices for such applications, there is a critical need for robust 2D magnets with ordering temperatures above room temperature that can be created via exfoliation. Here the study of exfoliated flakes of cobalt substituted Fe5GeTe2 (CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 81 publications
7
43
1
Order By: Relevance
“…Bulk Fe 5 GeTe 2 crystals exhibit multiple-step magnetic transitions with decreasing temperature ( T ). , Determined from the sudden increase in the T -dependent magnetization ( M ) measured under a small magnetic field ( H ) of 50 Oe, the T c in our samples is 313 ± 5 K (Figure c). Recent work shows that the T c can be significantly enhanced via partial replacement of Fe by Ni . At around 120 K, another feature appears on M as manifested by a prominent slope change for H || ab (Figure c); correspondingly, the resistivity curve (Figure b) shows a remarkable decrease at the same temperature.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Bulk Fe 5 GeTe 2 crystals exhibit multiple-step magnetic transitions with decreasing temperature ( T ). , Determined from the sudden increase in the T -dependent magnetization ( M ) measured under a small magnetic field ( H ) of 50 Oe, the T c in our samples is 313 ± 5 K (Figure c). Recent work shows that the T c can be significantly enhanced via partial replacement of Fe by Ni . At around 120 K, another feature appears on M as manifested by a prominent slope change for H || ab (Figure c); correspondingly, the resistivity curve (Figure b) shows a remarkable decrease at the same temperature.…”
mentioning
confidence: 92%
“…Recent work shows that the T c can be significantly enhanced via partial replacement of Fe by Ni. 16 At around 120 K, another feature appears on M as manifested by a prominent slope change for H || ab (Figure 1c); correspondingly, the resistivity curve (Figure 1b) shows a remarkable decrease at the same temperature. These observations suggest a second magnetic transition taking place at T* ∼ 120 K, which has been identified as the ordering temperature of the Fe1 sublattice (whereas Fe2 and Fe3 moments order at T c ≈ 313 K); 14,17 this transition at T* is also revealed to be strongly coupled to the lattice 14,17 and coincides with a Lifshitz transition in the electronic structure 18 and thus has a significant impact on the charge transport.…”
mentioning
confidence: 93%
“…The properties of 2D magnets, such as the Fe n GeTe 2 ( n = 3, 4, 5) family, CrI 3 , and Cr 2 Ge 2 Te 6 , , persist even down to thicknesses of one or several monolayers, , which could push magnetic memory information storage to the atomically thin limit. Among these vdW ferromagnets, Fe 5 GeTe 2 (FGT) was reported to possess a relatively high Curie temperature (270–310 K) and large saturation magnetization (∼700 kA/m), exhibiting prospects as a candidate for room-temperature 2D vdW devices.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study reported a record high T c of 478 K in Ni‐doped Fe 5 GeTe 2 . [ 85 ] All the results reveal that Fe 5 GeTe 2 is an ideal platform to realize high‐temperature skyrmions with tunable spin topology.…”
Section: Resultsmentioning
confidence: 99%